Multi-Walled Carbon Nanotubes Mediated Thin-Layer Chromatographic Enantioseparation of Ofloxacin - Huang, Dushu; Yu, Jingang; Liu, Wei; Li, Zijing; Yi, Zhongzhou; Wu, Jie (Current Nanoscience, 2013)
To enantioseparate ofloxacin, we demonstrated a new method of using multi-walled carbon nanotubes (MWCNTs) impregnated thin-lay chromatography (TLC). A general discussion that focuses on the possibility of CNTs in the field of chromatographic enantioseparation is presented. We hope it will be useful for the chromatographer and pharmaceutical industries.
Keywords: enantioseparation